Training Needs Analysis: Suggested Framework for Identifying Training Need - Rahmana, Arief; Sukaya, Yaya (International Journal of Psychosocial Rehabilitation, 2020)
Training needs analysis (TNA) can be considered the process of identifying and gathering data to determine what training needs exist based on performance gaps so that training can be developed to help the organization accomplish its objective. TNA was very useful as a fundamental to the success of the training program. Without conducting need analysis, effective training can’t be achieved, and organizations run the risk of overdoing training, doing too little training, or missing the point completely. The main stage of TNA involves a number of logical steps: identify problem needs, determine the design of need analysis, collect data, analyze data, and provide feedback. This paper hopes to contribute to the body of knowledge on TNA by developing conceptual framework which provides guidelines for TNA implementation in training program